Families of Disjoint Sets Colouring Technique and Concept of Common Face and Non-Common Face (المجلة الدولية للبحوث العلمية, 2025)
Families of disjoint sets colouring technique is trial to generalize all type of colouring and partition. This paper related to face colouring, in this paper we introduce the concept of common face and non-common face, and used two methods to determine adjacency of faces. We introduce some results related to the concept of common face and results related to non-common face, and introduce some results explain the number of minimum colour classes not changed after addition or after removal of non-common face, if maximum clique number is constant.